2012
DOI: 10.1007/s00420-012-0834-9
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A concentrations in maternal breast milk and infant urine

Abstract: Purpose The present report describes the distribution of breast milk and urinary free and total bisphenol A (BPA) concentrations, from 27 post-partum women and their 31 infants, and explores the influence of age, sex, and nutritional source on infant BPA urinary concentration. Methods Both free (unconjugated) and total (free plus conjugated) BPA concentrations from women’s breast milk samples and infants’ urine samples were measured by online solid-phase extraction coupled to high-performance liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 39 publications
4
92
0
2
Order By: Relevance
“…These results indicated that our method is more sensitive than those previously reported, which measured BPA without any derivation process. 9,18,[32][33][34] The recoveries (%) for BPA at three spiked levels (0.50, 1.0, 10.0 μg/L) were 82.2, 88.9 and 85.1, respectively; further, the relative standard deviations (RSD, %) were 15.9, 4.2 and 1.8, respectively. Carryover tests indicated that there was no BPA detected in all three blank samples, which implied that there were no BPA residues in trap column or analysis column.…”
Section: Methods Performancementioning
confidence: 99%
See 3 more Smart Citations
“…These results indicated that our method is more sensitive than those previously reported, which measured BPA without any derivation process. 9,18,[32][33][34] The recoveries (%) for BPA at three spiked levels (0.50, 1.0, 10.0 μg/L) were 82.2, 88.9 and 85.1, respectively; further, the relative standard deviations (RSD, %) were 15.9, 4.2 and 1.8, respectively. Carryover tests indicated that there was no BPA detected in all three blank samples, which implied that there were no BPA residues in trap column or analysis column.…”
Section: Methods Performancementioning
confidence: 99%
“…18 The distinct exposure differences may be because of the different life style, age and regional different BPA usage. Although the BPA concentrations in the infants are generally lower than in the old children and adults, 9,18,34,35 because of their much greater susceptibility, the health risk needs to be investigated closely.…”
Section: Bpa Concentration In Infant Urine Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…A limited number of studies have assessed whether breastfeeding is associated with exposure of young children to BPA or phthalates, of which none reported any significant associations (46,49,54). Although BPA and phthalates partition into breast milk, unlike PBDEs they do not accumulate in breast milk (9,54,89).…”
Section: Dietmentioning
confidence: 99%